Accenting Lipid Peroxidation - Atukeren, Pınar (IntechOpen, 2021)
Lipid peroxidation can occur via either enzymatic or nonenzymatic reactions due to excess production of free radical molecules. This process culminates in cellular damage causing various diseases. This book examines lipid peroxidation as a current and future biomarker of oxidative stress.